„Wileński świat” Zygmunta Augusta w monografii miasta pióra Józefa Ignacego Kraszewskiego - Manyś, Bernadetta (Studia Europaea Gnesnensia, 2016)
The article aims to characterise the “Vilnius world” of king Zygmunt II August, as presented in a study of history of the Lithuanian capital written Józef Ignacy Kraszewski. The author attempts to show what kind of an image of Vilnius and its inhabitants in the times of the last Jagiellon was conveyed by Kraszewski in his description.